Voltage stability analysis considering dynamic interaction for power systems integrated with multi-PMSGs - Cheng, Lin; Wang, Jili; Ke, Xianbo; Han, Zhiyong; Ai, Dongping (Frontiers in Energy Research, 2024)
This paper presents the dynamic voltage stability index based on the voltage oscillation loop for power systems integrated with multiple permanent magnet synchronous generators (PMSGs) to assess the dynamic interaction on voltage stability. First, the model of power systems integrated with multi-PMSGs using a Q–V sensitivity matrix as feedback to connect all PMSGs is established. The transfer function model between voltage and reactive power is derived, and the voltage oscillation loop can be derived, which exists in each PMSG. Next, the dynamic voltage stability index is theoretically derived and given, the impact of dynamic interaction among multi-PMSGs on voltage stability can be quantified, and the source of voltage oscillation can be identified and determined. Then, the voltage stability is recovered by shedding the trouble-making PMSG. The parameters of PMSGs could be tuned with the guidance of the dynamic voltage stability index to reduce the risk of voltage oscillation. Finally, the example of a test system with PMSGs is used to validate the correctness of the dynamic stability index.